Characteristics in Classification of Information Use (IU) - Albarda Albarda (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Conventionally, information quality or IQ used in most researches and also in practice as dimensions of characteristics which inherent in valuable information. IQ is characteristic measures based on information production processes. As a result, it may not be a valuable for its users and even for enterprise value. Our approach is to define a new information characteristic based on process of information consumption or usage, called IU as complement to IQ. The characteristics in IU consists of two dimensions ie: (i) conformity on repackaging and (ii) originality on exchange information for users. Parameters for this dimensions acquired using features extraction from IU process in each layer of enterprise management. The paper also describes how to apply the new characteristics practically to provide a higher information values for enterprise.